[OP.LB.02.07] BLOOD PRESSURE AND HEXADECANEDIOATE: DISSECTING FUNCTIONAL PATHWAYS. (September 2016) - Menni, C.; Metrustry, S.; Ehret, G.; Dominiczak, A.F.; Chowienczyk, P.; Spector, T.D.; Padmanabhan, S.; Valdes, A.M.
Abstract : Objective: The dicarboxylic fatty acid hexadecanedioate is functionally associated with increased blood pressure. The aims of this study was to further characterize which pathways are related to this compound using genetic and transcriptomic data. Design and method: A genome-wide association scan (GWAS) was conducted on 6447 individuals from the TwinsUK and KORA cohorts. SNPs achieving genome-wide significance were then tested in the International Consortium for Blood Pressure and in a GWAS of extremes of blood pressure. Transcriptomic analyses in adipose tissue were further performed. Results: 242 SNPs mapping to two independent genome-wide significant signals were found. In rs414056 in the SCLO1B1 gene (P < 1 x 10[−51]), the high risk myopathy allele C is associated with higher levels of hexadecanedioate. In the same gene rs11045656 is associated with both higher hexadecanedioate and higher risk of hypertension in a GWAS of blood pressure. The second signal mapped to the cytochrome 4 cluster in chromosome 1 previously implicated in hypertension via natriuretic 20-HETE. Hexadecanedioate levels also correlate with adipose tissue gene-expression of CYP4 probes (P < 0.05) and of alcohol dehydrogenase probes (Beta (SE) = 0.12(0.02); P = 6.04 x 10[−11]). Conclusions: Circulating hexadecanedioate levels are strongly influenced by a functional gene variant involved in hepatic uptake of organic anions. Levels are also affected by the first two enzymes in the omega-oxidation pathway. All three genes identified (SLCO1B1, ADH1B, and CYP4A11) have been previously implicated in risk of hypertension particularly in Asians, which suggests hexadecanedioate could be a useful intermediate phenotype for the study of blood pressure regulation. Moreover, the novel and strong association of hexadecandedioate with SLCO1B1 merits further studies because of its known association with statin therapy.